1997
DOI: 10.1111/j.1432-2277.1997.tb00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-specific protein (PASP), serum amyloid A [SAA), and neopterin (NEOP) in the diagnosis of rejection after simultaneous pancreas and kidney transplantation

Abstract: A reliable, noninvasive indicator of pancreatic allograft rejection is urgently needed. In this study, serum (S), plasma (P), and urine (U) levels of pancreas-specific protein (P-PASP, U-PASP), neopterin (S-NEOP, U-NEOP), amylase (U-AMYL), and amyloid A (SAA) were measured daily in ten type I diabetic patients following simultaneous pancreas and kidney transplantation (SPK). Rejection episodes occurred in three isolated pancreas, nine isolated kidney, and five simultaneous pancreas and kidney transplants. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In the present study, a mass value of 1132 Da was identified as SAA1 with the sequence of EAFQEFFGR, which is identical to the reported biomarker peptide identified in the plasma of mice bearing tumors established from human gastric cancer cell lines 3. Elevated levels of SAA have been reported in the plasma/serum of mice bearing intestinal tumors 4 and neuroblastomas 6, as well as in sera of patients with various types of human cancers including nasopharyngeal 29, prostate 30, pancreatic 31.…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, a mass value of 1132 Da was identified as SAA1 with the sequence of EAFQEFFGR, which is identical to the reported biomarker peptide identified in the plasma of mice bearing tumors established from human gastric cancer cell lines 3. Elevated levels of SAA have been reported in the plasma/serum of mice bearing intestinal tumors 4 and neuroblastomas 6, as well as in sera of patients with various types of human cancers including nasopharyngeal 29, prostate 30, pancreatic 31.…”
Section: Discussionsupporting
confidence: 81%